Degradation analysis of doped organic p-n heterojunction charge generation layers by impedance and optical spectroscopy. (September 2021) - Gasonoo, A.; Lim, Y.-J.; Jang, E.-J.; Lee, J.; Kim, M.-H.; Choi, Y.; Lee, J.-H.
Abstract: Investigation of the long-term stability of charge generation layers (CGLs) provides a fundamental and an essential approach in achieving highly efficient tandem organic electronic devices. Thus, in this foremost study, the degradation mechanism of electrically aged organic p-n heterojunction CGLs has been investigated by impedance and optical spectroscopy. Rubidium carbonate (Rb2 CO3 )–doped 2, 2, 2-(1, 3, 5-benzinetriyl)-tris(1-phenyl-1H-benzimidazole) (TPBi) and molybdenum trioxide (MoO3 )–doped 1, 4-bis[N-(1-naphthyl)-N′-phenylamino]-4, 4′-diamine (NPB) are used as the n-type and p-type organic semiconductors, respectively. A detailed analysis from capacitance-frequency ( C–F ) and capacitance-voltage ( C–V ) characteristics reveals reduced charge generation and 19.6% reduction in the geometric capacitance of the CGL after electrical aging. Reduced peak intensity from UV–Vis–NIR spectra of the aged CGL points to 21.4% charge transfer complex decomposition of the Rb2 CO3 -doped TPBi. We propose that the rate-limiting step of charge generation in the CGL is caused by the electron transport in the TPBi:Rb2 CO3 layer and not the charge generation itself at the TPBi:Rb2 CO3 /NPB:MoO3 heterojunction. This simple, comprehensive, and non-destructive technique facilitates a crucial analysis that underpins the mechanism of device degradation and further provides a fundamental approach in developing highly stable CGLs for efficient organic electronic devices. Graphical abstract: Image 1 Highlights: The degradation mechanism of the electrically aged charge generation layer (CGL) is analyzed. Impedance spectroscopy pointed the reduction in geometric capacitance after aging. UV–Vis–NIR spectroscopy confirmed the reduced charge transfer complex after aging. Rate-limiting of the CGL is caused by the electron transport in the TPBi:Rb2CO3 layer. The non-destructive electrical and optical analysis method is successfully demonstrated.